Caring for One of Our Own. (10th April 2014) - Schapira, Lidia; Blaszkowsky, Lawrence S.; Cashavelly, Barbara J.; Kim, Christina Y.; Riley, John P.; Wold, Mali C.; Ryan, David P.; Penson, Richard T.
Abstract: Schwartz Center Rounds are monthly multidisciplinary meetings where caregivers reflect on important psychosocial issues that they, along with patients and their families, face and gain insight and support from fellow staff members, with the goal of advancing compassionate health care, supporting caregivers, and fostering the connection between a clinician and his or her patients. This Schwartz Round focused on boundaries and the particular privileges and pressures of caring for a member of the staff. The article explores the tension between professional courtesy and empathic engagement. Major transitions can include the intrinsic fear of abandonment. Being "connected" is an important aspect of the patient-caregiver relationship. Patient-centered care requires that we balance clinical acumen and medical technology with humanism throughout the different phases of a patient's experience with a life-threatening illness. Abstract : This article focuses on the particular privileges and pressures that caregivers face when caring for a fellow staff member, exploring the boundaries between professional courtesy and empathic engagement.